Diffusion Magnetic Resonance Imaging Detects Progression in Parkinson's Disease: A Placebo‐Controlled Trial of Rasagiline. Issue 2 (1st November 2021) - Arpin, David J.; Mitchell, Trina; Archer, Derek B.; Burciu, Roxana G.; Chu, Winston T.; Gao, Hanzhi; Guttuso, Thomas; Hess, Christopher W.; Lai, Song; Malaty, Irene A.; McFarland, Nikolaus R.; Pasternak, Ofer; et al.
Abstract: Background: Rasagiline has received attention as a potential disease‐modifying therapy for Parkinson's disease (PD). Whether rasagiline is disease modifying remains in question. Objective: The main objective of this study was to determine whether rasagiline has disease‐modifying effects in PD over 1 year. Secondarily we evaluated two diffusion magnetic resonance imaging pulse sequences to determine the best sequence to measure disease progression. Methods: This prospective, randomized, double‐blind, placebo‐controlled trial assessed the effects of rasagiline administered at 1 mg/day over 12 months in early‐stage PD. The primary outcome was 1‐year change in free‐water accumulation in posterior substantia nigra (pSN) measured using two diffusion magnetic resonance imaging pulse sequences, one with a repetition time (TR) of 2500 ms (short TR; n = 90) and one with a TR of 6400 ms (long TR; n = 75). Secondary clinical outcomes also were assessed. Results: Absolute change in pSN free‐water accumulation was not significantly different between groups (short TR: P  = 0.346; long TR: P  = 0.228). No significant differences were found in any secondary clinical outcomes between groups. Long TR, but not short TR, data show pSN free‐water increased significantly over 1 year ( P  = 0.025). Movement Disorder Society Unified Parkinson's Disease Rating Scale testing of motor function, Part III increased significantly over 1 year ( P  = 0.009), and baseline free‐water in the pSN correlated with the 1‐year change in Movement Disorder Society Unified Parkinson's Disease Rating Scale testing of motor function, Part III ( P  = 0.004) and 1‐year change in bradykinesia score ( P  = 0.044). Conclusions: We found no evidence that 1 mg/day rasagiline has a disease‐modifying effect in PD over 1 year. We found pSN free‐water increased over 1 year, and baseline free‐water relates to clinical motor progression, demonstrating the importance of diffusion imaging parameters for detecting and predicting PD progression. © 2021 International Parkinson and Movement Disorder Society